Who Do We Think We Are? Library Sector Populations in Australia. Issue 4 (2nd October 2018) - Magnussen, Amanda
ABSTRACT: A full census of Australian libraries has not been conducted for many years. Yet this does not remove the strategic importance for Australian libraries and library professionals to understand their context. This paper describes the methodology and results from a research project to map Australian libraries within their populations, and better understand the numeric composition of Australian library sectors. Sectoral information was gathered from identified Australian library peak associations, usually based on membership numbers. This information was then synthesised to minimise cross-sectoral overlaps and double-counting, and reach an estimated population count for each sector. Population estimates for some sectors were further compared against relevant directories and databases to corroborate findings where the accuracy of the source data was questionable. The resulting information paints a picture that is indicative of the extent of Australian library populations in early 2018.